Consumerscapes and the resilience assessment of urban retail systems - Cachinho, Herculano (2017)
Despite the plethora of studies on the behavior and values of consumers, research in the social sciences tends to sideline the role of the cultural dimension of consumption in the assessment of vitality and resilience of urban retail systems. However, given the tendency for retailers to make consumers a key element in their strategies, the cultural approach seems to be a valuable alternative to firm-centric analysis. This paper seeks to face this challenge mobilizing the lens of Consumer Culture Theory (CCT). The aim is to show why consumerscapes matter in the assessment of urban retail resilience. According to Arnould (2005), CCT allows us to capture the motivating social and cultural contexts of retail patronage and purchasing behaviors and the myriad of motivating factors behind the retail purchase decision. People have a variety of projects that they tend to realize through shopping practices and consumption, and retailers offer the range of resources they need to accomplish such projects. Bearing these ideas in mind, we suggest that in order to assess the resilience of urban retailing we need to know the extent to which the different shopping districts provide consumers with the range of resources they want so as to fulfill their projects, and how retailers and public authorities can, in the long term, sustain or improve the levels of consumer satisfaction. These ideas are discussed both in a theoretical and empirical way supported by the data collected from consumer surveys carried out in three neighborhood shopping districts in Greater Lisbon.